Culture and age influences upon gambling and problem gambling. (June 2015) - Subramaniam, Mythily; Abdin, Edimansyah; Shahwan, Shazana; Vaingankar, Janhavi Ajit; Picco, Louisa; Browning, Colette Joy; Thomas, Shane Andrew; Chong, Siow Ann
Abstract: Objective: This study aimed to (i) examine the prevalence and types of gambling, (ii) establish prevalence of 'pathological' gambling, (iii) explore the correlates of gambling, and (iv) establish psychiatric and physical comorbidity in a sample of older adult gamblers (≥ 60 years) in contrast to younger gamblers in a representative population sample in Singapore. Method: This paper reports the results of a secondary analysis of data from a representative community survey of 6616 participants, of which 2252 had engaged in gambling activities at least once in their lifetime. Results: 48.9% of older adults reported lifetime gambling. Older gamblers were more likely to be males, married or widowed (vs. never married), with pre-primary, primary and secondary education (vs. university), economically inactive (vs. employed) and had personal annual income of SGD 19, 999 and below (vs. SGD 50, 000 and above). Older gamblers had significantly higher rates of betting on horses, playing numbers or betting on lotteries, and playing Mahjong. After adjusting for demographic variables in multiple logistic regression analyses, gamblers aged 60 years and older had significantly lower odds of having pathological gambling than those in the younger age group (OR = 0.4). Older gamblers had significantly higher odds of having diabetes (OR = 3.2), hypertension (OR = 4.9), and any comorbid chronic physical condition assessed in this study. Conclusions: For the majority of older adults, gambling remains a recreational activity that is entertaining and a way of socialization. However, one must remain cognizant of the possible risks for some to develop disordered gambling. Highlights: 48.9% of older adults in Singapore reported lifetime gambling. Older gamblers were more likely to be males, married or widowed, and had lower education. Older gamblers had significantly lower odds of having pathological gambling.